Using in situ seed baiting technique to isolate and identify endophytic and mycorrhizal fungi from seeds of a threatened epiphytic orchid, Dendrobium friedericksianum Rchb.f. (Orchidaceae) - Khamchatra, Na-monrug; Dixon, Kingsley; Chayamarit, Kongkanda; Apisitwanich, Somsak; Tantiwiwat, Sureeya (Agriculture and Natural Resources, 2016)
All orchids require association with mycorrhizal fungi for seed germination and development under natural conditions but their identification and feasibility are not known. The in situ seed baiting germination was examined of Dendrobium friedericksianum Rchb.f., a native threatened epiphytic orchid species, to detect fungi that promote germination. It was found that seed germination percentages were lowered by 0.1%, with a total of seven protocorms formed. Six endophytic fungi were isolated from seven protocorms in seed packets. Three binucleate Rhizoctonia-like fungal isolates which formed a teleomorphic state were morphologically identified as Tulasnella violea, Epulorhiza repen (anamorph Tulasnella) and Trichosporiella multisporum. The species of Beauvaria and Fusarium which are endophyte fungi were also isolated and may play an important role for plant growth and survival of D. friedericksianum. The results in this study suggested that in situ seed baiting is beneficial for screening compatible mycorrhizal fungi to promote the growth and propagation of epiphytic orchids.